Suppression of Ambiguity of Phase Interferometer with Extended First Base - Zálabský, Tomáš; Hnilička, Tomáš (Croatian Society Electronics in Marine - ELMAR, 2018)
This paper discusses the design of an interferometric system with extended first base, that the role of a passive precision approach radar should perform. The topology of the interferometric system is designed. The method of detecting the angle of arrival of the signal is proposed. The main goal is to propose an algorithm for suppression of uncertainty of determination of angle of arrival. The system based on comparison of the results of determining the angle of signal arrival using the first and second bases is discussed. Based on this comparison, results obtain from third base are assigned. These results guarantee accurate and unambiguous determining the direction of signal arrival. Possibilities for further expansion are discussed.
Potlačení nejednoznačnosti fázového interferometru s prodlouženou první bází
Keywords: Phase Interferometry; Precision Approach radar; Radar; Fázová interferometrie; Přesný přistávací radar; Radar